MOTIVATION TO USE M-PAYMENT IN SHOPPING CENTRE: A QUALITATIVE INQUIRY - Efendi Efendi; Lina Salim (Universitas muhammadiyah malang, 2020)
The study intends to understand motivation to use M-payment in shopping centre, which can be considered to be a new technology of payment. The literature on technology acceptance has been flourishing for a long time. The three leading theories in technology acceptance are innovation diffusion, technology acceptance, and network externalities theories. The study employs a qualitative methodology using the approach of photo voice. Six participants were selected for the study. The results of the study indicate that the participants are motivated to use M-payment because of convenience, sales promotion, convergence, and keeping up with the trend or technology. The findings are then compared to the leading theories in technology acceptance.